Reforming Agricultural Development Banks - Thorsten Giehler; Hans Dieter Seibel; Stefan Karduck (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2005)
The issue of agricultural development banking discussed in this paper has a history to it. For a hundred years or more, until the middle of the 20th century, a small number of agricultural banks existed outside of Europe. During that period, 15.5% of the banks in the AgriBank-Stat inventory, were established.1 Some seem to have led an inconspicuous life, like the predecessors of the Agricultural Cooperative Bank in Syria and the Agricultural Credit Corporation in Jordan, established in 1888. Others, like the predecessor of Bank Rakyat Indonesia dating back to 1885, were at the center of lively debates over such issues as centralized vs. decentralized rural banking; the role of the government as a decision-maker vs. the people themselves, perhaps organized in cooperatives; and banking in kind vs. banking in money.3 However, whatever lessons might have been drawn from that experience appear to be lost in history.
Keywords: 330